Women's Language Features of Jules Ostin in The Intern Film - Nur Amalia Fhadila Putri; Setya Ariani; Jonathan Irene Sartika Dewi Max (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research aims to identify the women’s language features of Jules Ostin utterances based on Lakoff’s theory and to identify language functions served by women’s language features of Jules Ostin based on Jakobson’s theory. This research was conducted by using descriptive qualitative research. From ten features of women’s language, the researcher found nine features used by Jules Ostin in The Intern film. They were lexical hedges or fillers, tag questions, rising intonations on declaratives, empty adjectives, precise color terms, intensifiers, super polite forms, avoidance of strong swear words, and emphatic stress. The first frequent of women’s language features that Jules Ostin used lexical hedges or fillers, and the second frequent of women’s language features that Jules used intensifiers. Meanwhile, hypercorrect grammar did not occur in this research because Jules used informal language in her utterances to shorten the gap between Jules and the others character. Then, there are language functions served by women’s language features by Jules Ostin’s utterance in The Intern film. They were expressive function, directive function, and metalinguistic function. Jules used expressive function to express her feelings such as, lack of confident, being unsure, and gratitude. Jules used directive function because it contains commands and requests. The purpose of Jules using the mentioned of metalinguistic function was to clarify about her ideas.